Characterization of hetero-epitaxial Ge films on Si using multiwavelength micro-raman spectroscopy - Yoo, Woo Sik (2015)
To meet various physical property requirements of materials for advanced applications for specific devices, combinations of Si/Ge, Ge/Si, Si1-xGex/Si, are frequently introduced in the device fabrication process. Epitaxy, condensation and annealing processes are commonly used. Since a small variation in composition, strain and crystallinity can result in reduced device performance or failure, the composition, strain and crystallinity must be carefully monitored and controlled throughout the manufacturing process. We have studied the dependence of Ge and Si intermixing on annealing temperature and Raman excitation wavelength. Using multiwavelength Raman spectroscopy, we found Ge and Si intermixing in epitaxially grown Ge(100)/Si(100) after successive thermal anneals. Very strong dependence of signal-to-noise (S/N) ratio measurements on excitation wavelength and film structure was observed. Suitable excitation wavelengths must be chosen to properly characterize Si and Ge-based heteroepitaxial layers based on the thickness, stacking order and composition of epitaxial films having different optical properties at different wavelengths.